132 Intraoperative, High-Resolution Electrocorticography Mapping in Parkinson Patients During a Reaching Task Supports a Compensatory Role for Sensorimotor Cortical Oscillations in the Low-Dopamine State. (August 2015) - Rowland, Nathan Christopher; de Hemptinne, Coralie; Swann, Nicki; Qasim, Salman; Miocinovic, Svjetlana; Ostrem, Jill L.; Knight, Robert T.; Starr, Philip A.
Abstract : INTRODUCTION: In Parkinson patients in the OFF medication state, basal ganglia local field potentials exhibit characteristic changes in beta and gamma oscillations that may be directly related to the symptoms of rigidity and bradykinesia. However, magnetoencephalography and low-resolution electrocorticography (ECoG) studies of sensorimotor cortex suggest that changes in cortical oscillations in Parkinson patients may differ from those of the basal ganglia during the OFF medication state. METHODS: To further explore sensorimotor cortex oscillatory activity in Parkinson disease (PD), we performed high-resolution ECoG (2-6 contacts per gyrus and 1-2 contacts per sulcus) recordings intraoperatively in patients undergoing deep brain stimulator placement in the awake state. We analyzed ECoG potentials during a computer-controlled task designed to separate movement preparation from movement execution and compared findings with similar invasive recordings in patients with essential tremor (ET), a condition not associated with rigidity or bradykinesia. RESULTS: We show that (1) cortical beta spectral power is not different between PD and ET patients, (2) motor preparation in Parkinson patients in the OFF medication state is associated with increased cortical beta reactivity compared with patients with ET, and (3) cortical broadband gamma power is elevated compared with ET patients during both rest and task recordings. CONCLUSION: Our findings are suggestive of an inverse oscillatory profile in the sensorimotor cortex of Parkinson patients that, in contrast to basal ganglia, may act to facilitate movement in the face of an antikinetic bias inherent in the dopamine-depleted state.